The Development Of An Oversight And Accountability Framework For Municipalities In The Free State Province - Sebakamotse, Jermia, Khahliso, Teboho (Central University of Technology, Free State, 2020)
Section 152 of the Constitution of the Republic of South Africa, 1996 mandates that local communities receive democratic and accountable governance and they and community organisations’ involvement in the matters of local government should be encouraged. In terms of Section 4(2) of the Municipal Systems Act (MSA), 2000, the municipal council is the executive and legislative authority of the municipality and must use its resources in the best interests of the local community. The municipal council, as the highest authority in the municipality, has significant powers of approval and oversight responsibilities. As such, the speaker, as the chairperson of the municipal council, fulfils a critical oversight role to hold the political executives to account for their actions. The mayor (if the municipality has an executive committee) or executive mayor (if there is no executive committee) is the political leader who directs the fiscal and financial matters of the municipality. Section 56(3)(e) provides that the executive mayor must oversee service provision in the municipality and ensure that it is sustainable. It was highlighted in this study that, in terms of Section 59 of the MSA of 2000, it is incumbent on the municipal council to develop a system of delegation that maximises the administrative and operational efficiency of the municipality. This section also provides for adequate checks and balances and empowers the municipal council to delegate certain powers to perform any of the municipality’s duties to any other political structure, political office-bearer, councillor, or staff member of the municipality and, likewise, to withdraw any delegation or instruction. In terms of Section 60 of the Municipal Financial Management Act (MFMA), 2003, the municipal manager (MM) is the accounting officer of the municipality and he/she is accountable for the effective and efficient management of all municipal funds received and all payments made by the municipality. The MM, as the accounting officer of the municipality, fulfils a key accountability role to promote the sound financial management of the municipality. It is clear that while political office-bearers (mayor or executive mayor, speaker, municipal councillors) are responsible for overseeing the financial and administrative performance of the municipality, the municipal council holds the accounting officer and relevant municipal officials to account for the manner in which they manage the financial and administrative matters or the municipality. Despite numerous legislative prescripts and the establishment of mandated oversight and accountable structures, all the municipalities in the Free State province failed to provide accountable local government to their communities. This was attested by the 2017-2018 Auditor-General’s audit report that the financial positions of all the municipalities (100%) of the Free State province had deteriorated to the extent of total breakdowns in financial controls. The Auditor- General reports for 2016-2017 and 2017-2018 warned that the blatant disregard for controls and compliance with key legislation have led to deteriorating accountability and leadership failures (AGSA, 2018:55; AGSA, 2019:12). The deterioration of all the Free State province municipalities’ financial position is proof that citizens failed to hold functionaries to account for poor performance. It was argued in this study that the weak control environment in municipalities in the Free State province led to a lack of consequences and poor oversight and accountability. Thus, there is an urgent need to ensure that the political oversight structures and MM give effect to the constitutional obligations to involve community members and community organisations in the affairs of local government. The aim of the study was to positively contribute to instituted oversight and accountability in municipalities in the Free State province by developing a framework for oversight and accountability that promotes democratic local governance. The objective with this proposed framework was to provide a holistic and coherent approach by identifying key statutory and legislative frameworks, policies, regulations, structures, role players as well as support and enforcement structures required to promote political, financial, administrative and social oversight and accountability within municipalities of the Free State province. Oversight structures must ensure consequences for non-compliance with legislation, policies, regulations, serious maladministration in connection with the affairs of municipalities, and other transgressions and irregularities. To be effective, enforcement agencies should conduct investigations of any reported transgressions and take required disciplinary steps. The proposed framework promotes consequences for non-compliance and non- performance in that mayors, accounting officers, chief financial officers (CFOs) and relevant officials in municipalities should be accountable for any financial losses incurred by municipalities during their term in office. As indicated in the framework, political office-bearers should give effect to the constitutional mandate to promote accountable local government to local communities. In addition to the proposed framework for oversight and accountability, this study contained specific recommendations to promote effective oversight and accountability. The first was that all municipalities in the Free State province should comply with the provisions of the Constitution of 1996 together and other applicable local government legislative frameworks, policies and supply chain management (SCM) regulations, with defaulters held accountable for their actions. Thus, there must be consequences for non-compliance with the afore mentioned. In addition, municipal councillors should adhere to Section 11(a) of the Code of Conduct of Councillors as provided in Schedule 1 of the MSA, 2000 which stipulates that a councillor may not, unless determined by law and mandated by council, interfere in the management or administration of any department of the municipal council. Here also, defaulters should be held to account for their actions. Moreover, municipal councils should adhere to Section 152(1) of the Constitution, 1996 which provides the objectives of local government. Furthermore, the oversight roles of the speaker, municipal council, mayor or executive mayor and municipal public accounts committee (MPAC) should be strengthened in municipalities of the Free State province to hold the executive to account and to ensure efficient and effective use of municipal resources. Likewise, the MM, as the accounting officer, should personally be held accountable for any loss of allocated funds or assets as a result of any deficiency in the administrative or managerial arrangements of the municipality. Consequently, failure to execute assigned responsibilities should result in the removal of the MM from office. The Public Audit Amendment Act, 2018, states that if the accounting officer fails to implement remedial action, the Auditor-General may issue a certificate of debt in the name of the relevant accounting officer. As a result, it is crucial that internal controls intended to prevent irregularities and deviations from the MFMA, 2003, and SCM regulations be strengthened in all municipalities of the Free State province. It was therefore recommended that more should be done to empower ward committees and strengthen their role to promote participatory governance and accountable local governance. Also, the South African Local Government Association (SALGA) should investigate the possibility to establish an independent local government ombudsperson to address the crisis of perennial service delivery protests in municipalities. Although no legislative prescripts make provision for a recall procedure, SALGA should investigate the possibility of the implementation of the recall procedure of councillors and mayors as a mechanism to improve public accountability in local government. In this way, delinquent political office-bearers could be recalled. Yet another step to ensure sound administrative and financial management within the municipality of the Free State province is the filling of key positions, such as senior manager, which are increasingly vacant. Lastly, provincial government should ensure that it supports and effectively monitors the performance of all municipalities within the Free State province. Specific recommendations were made from the empirical study to promote effective oversight and accountability in municipalities in the Free State province. One recommendation was that CoGTA should investigate a possible recall procedure. Concerns included that municipal elections could be used to revoke the electoral mandate of an elected official and that voters did not have any direct way of holding elected municipal representatives to account during the term for which were elected. This could be addressed by SALGA ensuring that all municipal councillors clearly understand their oversight role and the important role of portfolio committees, MPACs, audit committees and municipal performance audit committees in promoting oversight and accountability in the municipalities. As such, municipal councillors should receive training regarding the difference between oversight and political interference in the administration of the municipality. Speakers, mayors, executive mayors and municipal councillors should also receive training regarding key municipal legislations and SCM regulations to fulfil their oversight role effectively and ensuring that the municipal administration implements them. National and Provincial Treasury should ensure that functionaries unequivocally understand the MFMA of 2003. Mayors should understand their respective oversight roles in municipal financial management and administration and MMs ensure that the actions and conduct of administrative municipal staff agrees with the Code of Conduct for Municipal Staff Members in Schedule 2 of the MSA of 2000. The 2015-2016 Auditor-General report urged the Free State local government political and administrative leadership to take accountability for, and address, control weaknesses to improve audit outcomes. It is incumbent on the municipal council and mayor to ensure that the MM implements these recommendations as continued inaction weakens oversight and accountability of the financial affairs of most municipalities. Undoubtedly, more should be done to educate and inform local communities about the mandate of the local sphere.
Thesis